2021
DOI: 10.3389/fgene.2020.613217
|View full text |Cite
|
Sign up to set email alerts
|

New QTLs for Spot Blotch Disease Resistance in Wheat (Triticum aestivum L.) Using Genome-Wide Association Mapping

Abstract: Spot blotch disease caused by Bipolaris sorokiniana is a major constraint for wheat production in tropics and subtropics. The introgression of spot blotch resistance alleles to the disease susceptible lines is critical to securing the wheat production in these regions. Although genome-wide association studies (GWASs) for spot blotch were attempted earlier, the present study focused on identifying new quantitative trait loci (QTLs) for spot blotch under natural disease pressure in diverse field conditions. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 55 publications
(71 reference statements)
4
25
0
Order By: Relevance
“…An oxidative burst is triggered by recognition, accompanied by transcriptional reprogramming and HR, which leads to disease resistance (Thomas and van der Hoorn, 2018). QTL QSb.pau-2A mapped in the present study was found 55 Mb from QTL Q.Sb.bisa.2A (Tomar et al, 2021) and in same genomic region of QTL QSb.bhu-2A (Kumar et al, 2010) and is probably novel as this QTL had been contributed by A. speltoides while previously reported QTL are from cultivated wheat.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…An oxidative burst is triggered by recognition, accompanied by transcriptional reprogramming and HR, which leads to disease resistance (Thomas and van der Hoorn, 2018). QTL QSb.pau-2A mapped in the present study was found 55 Mb from QTL Q.Sb.bisa.2A (Tomar et al, 2021) and in same genomic region of QTL QSb.bhu-2A (Kumar et al, 2010) and is probably novel as this QTL had been contributed by A. speltoides while previously reported QTL are from cultivated wheat.…”
Section: Discussionsupporting
confidence: 47%
“…For BLUEs model, the genotypes were considered as fixed effects, while for BLUPs model all the effects were considered as random effects. Considering genotypes as random effects reduces the effect of screening time along with other environmental effects on SB severity (Tomar et al, 2021). The disease severity scores obtained by fitting the BLUPs and BLUEs models were plotted using ggplot2 v3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations